The Obesity Epidemic in the 21st Century - Szymocha, Monika; Bryła, Marek; Maniecka-Bryła, Irena (Polish Journal of Public Health, 2009)
Obesity is now considered a global civilization disease. Studies confirm its causal relationship with the occurrence of cardiovascular diseases, namely hypertension and coronary heart diseases, as well as type 2 diabetes, lipid disorders and some cancers. According to estimates about 200 million (50-65%) of Europeans are over-weight, a problem that increasingly affects children and adolescents. The development of civilization, and the change in human lifestyle, resulting in reduced physical activity, combined with the introduction of high-energy diet seem to be the most important causes of obesity, followed by genetic or environmental factors. Therefore, the need for the development of good health habits from early childhood should be particularly emphasized.Based on the review of the literature the following issues are presented in the work:• Epidemiological characteristics of obesity,• Forecasts for its prevalence in selected countries of the world,• Methods for assessing obesity in epidemiological studies,• Factors determining its presence in contemporary societies,• The correlation between the prevalence of obesity, with particular emphasis on visceral obesity, and other civilization diseases.• Recommendations for prevention.